Peripheral ossifying fibroma – case report - Lipczyński, Krzysztof; Pokrowiecki, Rafał; Zaleska, Małgorzata; Urbańczyk, Katarzyna (Journal of Stomatology, 2015)
Peripheral ossifying fibroma is a lesion of the gingival tissues representing up to 2 – 3% of all oral lesions that are biopsied. This tumour is seen very seldom and usually occurs in the gingiva of the front maxilla and resembles other epuli-like lesions. The treatment of choice is radical excision of the tumour. In cases when significant post-operative soft or hard tissue deficiency is present, reconstruction treatment by means of free tissue grafts or local flap surgery is required. Data from the literature indicates up to 20% recurrence of the tumour, especially following non-radical excision. Histologically, this tumour is composed of squamous epithelium, fibroblast component, foci of calcification and bone tissue in the centre. A rare case of peripheral ossyfying fibroma, which was localised in the oral vestibule in front mandible, is presented here. The lesion was present in the oral cavity for over twenty years. The surgical procedure is illustrated with photographic records and histopathological images of this case.